Mechanics of Fibrous Networks - Silberschmidt, Vadim V.; Silberschmidt, Vadim V. (Elsevier Science, 2022)
Mechanics of Fibrous Networks covers everything there is to know about the mechanics of fibrous networks, from basic analysis of simple networks to the characterization of complex cases of deformation, loading, damage and fracture. Looking at various types of fibrous materials, the book studies their microstructural characterization, quantification of their mechanical properties, and performance at fiber and network levels. In addition, the book outlines numerical strategies for simulation, design and optimization of fibrous products. Techniques for testing the mechanical response of these materials in different loading and environmental conditions are outlined as well. This comprehensive resource will aid readers in obtaining qualitative data for various fibrous networks. In addition, it will help them develop modeling strategies and fine-tune mechanical performance fibrous networks and products by changing their microstructure to develop new products with desired properties and performance. Discusses all the main features and characteristics of fibrous networks, including their microstructural characterization, quantification of their mechanical properties, and performance at the fiber and network level Covers both basic analysis of simple networks as well as complex cases of deformation, loading, damage and fracture of fibrous networks Outlines advanced numerical schemes for simulation, design and optimization of various fibrous materials